GENDER AND AGRARIAN QUESTION: THE DIVERSITY OF SOCIO-POLITICAL ACTION OF WOMEN IN THE FIELD - Ruscheinsky, Aloisio (Cadernos CERU, 1997)
The historical panorama of the rural women movement in the south of Brasil emphasizes the diversity on the social and political participation of them.